Технологический анализ стадии отгонки бензола в производстве нитробензола адиабатическим способом - Кондратов, Сергей Алексеевич; Хлякина, Татьяна Николаевна (НТУ "ХПИ", 2017)
Методами математического и компьютерного моделирования исследована эффективность стадии отгонки бензола и воды из смеси бензол-нитробензол-вода, которая образуется при адиабатическом нитровании бензола. Рассмотрено 3 модели организации удаления: непрерывная и периодическая дистилляция в вакууме и вакуум-ректификация. Установлено, что с точки зрения материального баланса и тепловых затрат наиболее выгодным является непрерывная вакуумная ректификация в колонне с 3 ступенями разделения.

The efficiency of the stage of distillation of benzene and water from the benzene nitrobenzene-water mixture, which is formed by adiabatic nitration of benzene, is studied with the help of mathematical and computer modeling methods. Three models of disposal organization are considered and analyzed with the help of numerical computer experiments: continuous and periodic distillation in vacuum and continuous vacuum rectification. The model equations were obtained taking into account the specific features of the processes. The first and third models describe stationary processes using systems of nonlinear algebraic equations. The second model describes the transient process using differential equations. In all models, it was assumed that, because of the low water content in the mass, the latter is completely in the vapor phase and completely goes to the distillate. In the continuous distillation model, it is provided that the distillate after condensation, including recycle reflux, is completely separated from water It has been shown that simple continuous vacuum distillation does not completely remove benzene from the vat liquid even at high molar ratios of the distillate-vat liquid. Periodic vacuum distillation and continuous distillation make it possible to obtain a distillate with a sufficiently low content of nitrobenzene and provide a low content of benzene in the vat liquid. It has been established that from the standpoint of material balance and heat costs, the most advantageous is continuous vacuum rectification in a column contained 3 levels of separation and a sufficiently low reflux ratio (~1,5). Distillate containing up to 2% nitrobenzene should be sent to the nitration stage. The vat liquid, commodity nitrobenzene contains not more than 0.1% benzene.
The technological analysis of the stage of benzene distillation in the manufacture of nitrobenzene by adiabatic method
Keywords: адиабатическое нитрование; вакуум-ректификация; математическое моделирование; adiabatic nitration; distillation stage; vacuum rectification